2016
DOI: 10.1186/s40729-016-0058-y
|View full text |Cite
|
Sign up to set email alerts
|

Relation between the stability of dental implants and two biological markers during the healing period: a prospective clinical study

Abstract: ObjectivesThe purposes of this study were to examine the correlation between the stability of dental implants and bone formation markers during the healing period and to monitor the stability of dental implants using the resonance frequency analysis (RFA) method. The null hypothesis of the study is no correlation between the stability of dental implant and bone formation markers.MethodsThe study is a prospective clinical study during the 3-month healing period of implant. At implant placement (PW Plus, Nakhon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
5
14
0
Order By: Relevance
“…A previous study of the relationship between the stability of PW Plus® dental implants and two biological markers during the healing period has shown that the mean implant stability quotient (ISQ) values decreased between 1 and 3 weeks after implantation. After 4 weeks, the ISQ values recovered to the initial values (Tirachaimongkol et al, ). These results are similar to those of Rabel et al, who showed high‐mean ISQ values immediately after implantation of Camlog® dental implants, and again, 3 months later (Table ; Rabel, Köhler, & Schmidt‐Westhausen, ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…A previous study of the relationship between the stability of PW Plus® dental implants and two biological markers during the healing period has shown that the mean implant stability quotient (ISQ) values decreased between 1 and 3 weeks after implantation. After 4 weeks, the ISQ values recovered to the initial values (Tirachaimongkol et al, ). These results are similar to those of Rabel et al, who showed high‐mean ISQ values immediately after implantation of Camlog® dental implants, and again, 3 months later (Table ; Rabel, Köhler, & Schmidt‐Westhausen, ).…”
Section: Discussionsupporting
confidence: 89%
“…Naturally, it is difficult, clinically, to quantify the magnitude and direction of the forces occurring in the surrounding bone during implant insertion (Guan et al, 2011) (Tirachaimongkol et al, 2016). These results are similar to those of Rabel et al, who showed high-mean ISQ values immediately after implantation of Camlog® dental implants, and again, 3 months later (Table 3; Rabel, Köhler, & Schmidt-Westhausen, 2007).…”
Section: Stress Distribution and Osteointegrationsupporting
confidence: 71%
See 2 more Smart Citations
“…Primary and secondary stability combine into total implant stability. Many studies have recorded total implant stability during the implant healing period, in order to monitor the process of osseointegration . A majority of those studies have revealed that implant stability decreases from the baseline, taken as the first day of placement of the implant.…”
Section: Introductionmentioning
confidence: 99%